Experimental and theoretical charge density, intermolecular interactions and electrostatic properties of metronidazole - Kalaiarasi, Chinnasamy; George, Christy; Gonnade, Rajesh G.; Hathwar, Venkatesha R.; Poomani, Kumaradhas (Acta Crystallographica Section B-Structural Science Crystal Engineering and Materials, 2019)
Metronidazole is a radiosensitizer; it crystallizes in the monoclinic system with space group P2(1)/c. The crystal structure of metronidazole has been determined from high-resolution X-ray diffraction measurements at 90 K with a resolution of (sin 0/lambda) max = 1.12 angstrom(-1). To understand the charge-density distribution and the electrostatic properties of metronidazole, a multipole model refinement was carried out using the Hansen-Coppens multipole formalism. The topological analysis of the electron density of metronidazole was performed using Bader's quantum theory of atoms in molecules to determine the electron density and the Laplacian of the electron density at the bond critical point of the molecule. The experimental results have been compared with the corresponding periodic theoretical calculation performed at the B3LYP/6-31G** level using CRYSTAL09. The topological analysis reveals that the N-O and C-NO2 exhibit less electron density as well as negative Laplacian of electron density. The molecular packing of crystal is stabilized by weak and strong inter- and intramolecular hydrogen bonding and H center dot center dot center dot H interactions. The topological analysis of O-H center dot center dot center dot N, C-H center dot center dot center dot O and H center dot center dot center dot H intra- and intermolecular interactions was also carried out. The electrostatic potential of metronidazole, calculated from the experiment, predicts the possible electrophilic and nucleophilic sites of the molecule; notably, the hydroxyl and the nitro groups exhibit large electronegative regions. The results have been compared with the corresponding theoretical results.
Keywords: atomic valence index; Electron density; Electrostatic potential; intermolecular interactions; metronidazole; radiosensitizer

Investigation of bond topological and electrostatic properties of plumbagin molecule: an experimental and theoretical charge density study - Kalaiarasi, Chinnasamy; Sivanandam, Magudeeswaran; Suganya, Suresh; Christy, George; Gonnade, Rajesh G.; Hathwar, Venkatesha R.; Kumaradhas, Poomani (Journal of Molecular Structure, 2020)
Plumbagin is a naturally occurring derivative with several medicinal properties including antioxidants, antifungal, antimalarial, leprosy and antitumor properties; their structural and electrostatic properties are yet to be determined. The crystal structure of plumbagin has been solved; it shows that the compound crystallizes in P2(1)/c space group with two molecules in the asymmetric unit. The electron density distribution of both molecules have determined from multipole model refinement. Among all the C-O bonds of both molecules (I & II), the OH group connected C-O bond and the methyl group connected C-C bond exhibits less electron density and the negative Laplacian of electron density as well. Further, the electrostatic potential (ESP) surface of two plumbagin molecules show some difference in their electronegative regions. The carbonyl O-atoms exhibit high electronegative ESP regions which are the key reactive locations of plumbagin when bind with the active site of target protein and in the ESP map, an aromatic pi-cloud also observed in one of the molecule. The electron density distribution of O-H center dot center dot center dot O intermolecular interactions between the molecules I and II, reveals that these interactions are found very stronger than the other interactions in the crystal. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Dipole moment; Electron density; Electrostatic potential; intermolecular interactions; Plumbagin